The Queen's Nurses collaborative inquiry - understanding individual and collective experiences of transformative learning. (June 2021) - McCormack, Brendan; Cable, Clare; Cantrell, Jane; Bunce, Alison; Douglas, Jane; Fitzpatrick, Julie; Forsyth, Nikki; Gallacher, Jeanie; Grant, Jen; Griffin, Lindsey; Guinnane, Christina; Hollis, Keri; et al.
No abstract available